The “Right” Definition for Post–Left Ventricular Assist Device Right Heart Failure: The More We Learn, the Less We Know - Hall, Shelley A.; Copeland, Hannah; Alam, Amit; Joseph, Susan M. (Frontiers in Cardiovascular Medicine, 2022)
Right heart failure is a major cause of morbidity and mortality following left ventricular assist device implantation. Over the past few decades, the definition proposed by the Interagency Registry of Mechanical Circulatory Support and Society of Thoracic Surgeons has continually evolved to better identify this complex pathology. We propose that the latest definition proposed by the Mechanical Circulatory Support Academic Research Consortium in 2020 will increase our recognition and understanding of this complex disease phenomenon.